Effect of Proton Pump Inhibitor Administration on Glycemic Parameters in Patients with Type 2 Diabetes Mellitus - Ebadi, Seyed Alireza; Pishgahi, Mehdi; Karimi Toudeshki, Kimia; Forootan, Mojgan; Ghanefard, Shirin; Shahrzad, Mohammad Karim (Archives of Men’s Health, 2021)
Introduction: Proton pump inhibitors can influence glucose-insulin homeostasis by elevating plasma gastrin. Considering the few clinical trials and contradictory results of previous studies, we aimed to evaluate the effect of omeprazole, a proton pump inhibitor, on glucose-insulin homeostasis in patients with type 2 diabetes mellitus (T2DM). Materials and Methods: In this before-after clinical trial, 40 patients with T2DM received omeprazole treatment for 12 weeks. Patients were asked to continue their diet, lifestyle, and physical activity throughout the study period. Glycosylated hemoglobin (HbA1c), fasting plasma sugar (FBS), insulin level, C-peptide and 2 hours post prandial blood sugar (2hppBS) were measured at baseline and after 12 weeks. Homeostatic model assessment of Insulin resistance (HOMA-IR) and homeostatic model assessment of β-cell dysfunction (HOMA-B) indices were also calculated at baseline and after 12 weeks of omeprazole administration. Results: After 12 weeks of omeprazole administration, there was a clear decrease in the mean HbA1C before (8.11±0.96) and after (7.13±0.68) the treatment (P<0.001). Similarly, a decrease in mean FBS and 2HPPBS before and after treatment was observed, which was statistically significant for FBS (P=0.01) but not for 2HPPBS (P=0.1). There was a clear increase in the level of Insulin (P=0.001) and C-peptide (P=0.003). The mean activity index of HOMA-B before and after receiving omeprazole was 54.41 27.06 and 79.24 45.32, respectively (P=0.007). Also, HOMA-IR index was 5 before, and 6 after receiving omeprazole (P=0.001). Conclusion: Administration of omeprazole, increases insulin levels and decreases the levels of HbA1c, FBS, thus improving glycemic status and can be combined with other drugs used to manage DM, especially in patients with gastrointestinal problems; but more studies are needed.